THE ROLE OF BEAUTY INFLUENCERS’ PERSONAL BRANDING IN SHAPING THE BRAND IMAGE OF STORE KDI IN KENDARI - Azis Muthalib, Dzulfikri (Pusat Studi Ekonomi, Publikasi Ilmiah dan Pengembangan SDM, 2025)
This study aims to examine the effect of Personal Branding on Brand Image at Store KDI in Kendari City. This research applies a survey method with a quantitative approach and an associative research strategy. The population in this study consists of 184,000 followers of Store KDI’s Instagram account, with a sample of 55 respondents determined using a non-probability sampling technique. Data were collected through an online questionnaire using a Likert scale and analyzed using simple linear regression with the help of SPSS version 25. The results show that Personal Branding has a positive and significant influence on Brand Image. These findings support theories and previous studies which state that influencers’ Personal Branding plays an important role in shaping consumers’ perceptions of brand image. Therefore, a strong Personal Branding strategy can be one of the key factors for Store KDI to build and maintain a positive brand image in the eyes of consumers.